2015
DOI: 10.1016/j.bjane.2013.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of positive pressure in preoperative and intraoperative of bariatric surgery and its effect on the time of extubation

Abstract: Background and objective: To investigate the influence of intraoperative and preoperative positive pressure in the time of extubation in patients undergoing bariatric surgery. Method: Randomized clinical trial, in which 40 individuals with a body mass index between 40 and 55 kg/m 2 , age between 25 and 55 years, nonsmokers, underwent bariatric surgery type Roux-en-Y gastric bypass by laparotomy and with normal preoperative pulmonary function were randomized into the following groups: G-pre (n = 10): individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The study by Baltieri et al [13] compared the use of PEEP 10 cmH 2 O versus PEEP 5 cmH 2 O and found no difference between the groups in LOS in the PACU, p = 0.21, (MD 36.00, 95% CI − 20.16 to 92.16; participants = 30; studies = 1; I 2 = 0%).…”
Section: Peep 10 Versus Peepmentioning
confidence: 97%
See 1 more Smart Citation
“…The study by Baltieri et al [13] compared the use of PEEP 10 cmH 2 O versus PEEP 5 cmH 2 O and found no difference between the groups in LOS in the PACU, p = 0.21, (MD 36.00, 95% CI − 20.16 to 92.16; participants = 30; studies = 1; I 2 = 0%).…”
Section: Peep 10 Versus Peepmentioning
confidence: 97%
“…In the blinding of participants and personnel domain all the studies were classified as high risk as the personnel could not be blinded. Four studies [7,13,17,25] adequately described the blinding of outcome assessment. Eleven studies [7,[14][15][16][17][18][19][20][21]24, 25] did not describe losses or exclusions which could cause imbalance between the groups.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…However, most of these trials were excluded from our final review because of the following reasons: 13 used different interventions; 10 were review articles, 6 did not meet our patient selection criteria, 5 lacked control group and 1 provided no outcome of interest. Thus, 13 trials were eligible for inclusion in this study [28,[40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Trial Characteristicsmentioning
confidence: 99%
“…Nine trials reported acceptable randomization methods. Outcome assessors were blinded to patient information in six trials [43,45,[47][48][49][50]. Outcome assessors were not blinded to patient information in the other seven trials.…”
Section: Trial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation